Hindrance to Benefit from the Potential Sources of Finance to Enhance the Growth of Small and Medium Size Enterprises in South Africa - Saah, Paul; Musvoto, Wedzerai S. (Journal of Reviews on Global Economics, 2020)
Small and Medium Size Enterprises are increasing playing an important role in economic development of most countries all over the world nowadays. For these small businesses to grow and be sustainable, they require sufficient capital in the form of financial resources to go operational because the lack of funding or access to finance could hamper their growth. The lack of access to finance has been reported to be one of the major causes of small business failure and discontinuity in South Africa. The purpose of this study is to identify the available sources of financial support for the growth of SMEs in South Africa. The study anticipates to find out why despite government’s effort to offer financial support for the growth of the SME sector, the rate of small business failure and discontinuity in South Africa is still one of the highest in the world. A qualitative methodological approach was utilized and interviews were conducted on SME managers on the subject under investigation. It was found that most SME managers in South Africa are ignorant about available sources of finance offered by government to boost the sector. It is imperative for the relevant authorities to revise and improve on the means and mechanisms used to support SMEs such that all small business managers are aware of the availability of this assistance and where and how to access it. In this regard, the government need to set up education and training facilities in different communities where intending and existing small business managers would be educated on the available sources of finance and how to access this funding to start up and grow their businesses.